A models of situational control by queries in the "client–server" systems - Боровик, В.М. (Proceedings of National Aviation University (archive), 2010)
A models of client-server is explored with as a system of mass service with situational priorities. Determine method to optimize the priorities and principles for practical application of research results in systems with distributed data processing.